Synthesis : . Synthesis : a newsletter for social ecology
Also subtitled: a newsletter for social ecology, and: a newsletter and journal for social ecology, deep ecology, bioregionalism, ecofeminism, and the green movement. - Since (1988):no.28 titled: Green synthesis. League for Ecological Democracy.